Innovation in Differentiated Learning Assisted by Digital Media Wordwall in Accommodating Elementary School Learning Needs - Yustin, Yustina Neny Hastuti; Sofyan Anif; Anatri Desstya; Minsih (Jurnal Elementaria Edukasia, 2025)
This research aims to describe the implementation of differentiated learning in elementary schools through the use of Wordwall digital media with the utilization of the open the box game feature. This research method uses a qualitative approach, with data collection techniques in the form of observation, interviews, and documentation of research subjects. Data validation uses source and technique triangulation techniques to ensure the validity of the findings. Data analysis was carried out through the stages of data reduction, data display, and verification. The results show that the use of Wordwall digital media with the utilization of the open the box game feature is able to accommodate the diverse learning needs of students so that it is often used in differentiated learning. The use of Wordwall digital media with the open the box feature is able to accommodate the diversity of student learning needs, both in terms of learning styles, levels of understanding, and learning interests. The stages of implementing this innovation involve planning materials tailored to students' learning categories, organizing activities on the Wordwall platform that support varied learning interactions, and reflecting on each stage of implementation to improve the relevance of learning. This media is a tool that is often utilized by teachers in carrying out differentiated learning because of its ability to provide various forms of interactive and interesting evaluation. This innovation has a significant impact in creating a learning environment that is responsive to the various learning needs of students, allows for variation in teaching strategies, and gives teachers flexibility in presenting materials more effectively.